EKSISTENSI CATUR KARO DITENGAH-TENGAH KEHIDUPAN MASYARAKAT KARO: STUDI KASUS PADA MASYARAKAT DESA SEBERAYA, DESA LINGGA, DAN DESA SUKAMBAYAK - Deni Chandra; Rony Edyanto Siburian; Lestari Dara Cinta Utami Ginting; Junita Setiana Ginting (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2023)
Chess is a board game with eight black squares and eight white squares that are mutually colorful. Chess is a very popular game in sharpening the brain. In Karo society, which is rich in tradition and culture, there is a karo chess game that has its own charm. In Karo society, this chess game has become part of the folklore of the Karo community itself. The purpose of this research is to analyze the existence of karo chess in Seberaya, Lingga and Sukambayak villages. Through a case study approach and historical research method with four stages, namely heuristics, verification, interpretation and historiography and data collected by researchers through interviews, observation and documentation. The results showed that in the midst of the development of conventional chess, the game of karo chess is still favored by the people of Seberaya, Lingga and Sukambayak Villages which are the objects of this research. Karo chess still exists in these villages and can still be seen in stalls around the neighborhood of the villagers who are the object of research, but not as big as in the past because conventional chess is more developed today. Karo chess is not just entertainment, but also teaches strategic values, perseverance, cooperation, and critical thinking skills of the players. Even so, the existence of Karo chess is faced with globalization that can reduce public interest, especially the lack of local government encouragement in introducing Karo chess. Therefore, efforts to maintain and popularize it are needed such as organizing tournaments, workshops, and training for the younger generation to promote this game to the public. Thus, the existence of Karo Chess in the Karo Community can be maintained as a valuable cultural heritage, as well as strengthening the cultural identity of the Karo tribe in this modern era